2016
DOI: 10.1016/j.ijscr.2016.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Extensive ossification of the paraspinal ligaments in a patient with vitamin D-resistant rickets: Case report with literature review

Abstract: HighlightsThis is the case of a 64-year-old woman with VDRR and extensive spinal ossification.This case was followed up for over 30 years.Imaging studies demonstrated fusion of the entire spine below the C2 vertebra.Mobility at the craniovertebral junction caused C1-level spinal cord compression.The pathology mimicked ankylosing spondylitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…26,27 A case report of vitamin D–resistant rickets found extensive ossification of the paraspinal ligaments. 28 The serum Pi concentration in most cases of rickets is lower than in normal controls. A recent study revealed that serum FGF-23 was higher in 41 male patients with OPLL than in 76 healthy male controls although the sample size was very small.…”
Section: Discussionmentioning
confidence: 97%
“…26,27 A case report of vitamin D–resistant rickets found extensive ossification of the paraspinal ligaments. 28 The serum Pi concentration in most cases of rickets is lower than in normal controls. A recent study revealed that serum FGF-23 was higher in 41 male patients with OPLL than in 76 healthy male controls although the sample size was very small.…”
Section: Discussionmentioning
confidence: 97%
“…The medical literature regarding the spinal manifestations of XLH and their surgical management and outcomes is restricted to case reports and short case series (Hirao et al 2016 ; Soehle and Casey 2002 ). Ossification of the paraspinal ligaments in XLH is well recognised and the published series document thickening of the laminae, calcification of the discs, facet joint hypertrophy and ossification of the ligamentum flavum and/or posterior longitudinal ligament (Hirao et al 2016 ; Soehle and Casey 2002 ; Dunlop and Stirling 1996 ; Velan et al 2001 ). These can result in spinal canal stenosis impinging on the spinal cord leading to myelopathy or on the lumbar nerve roots manifesting as neurogenic claudication/radiculopathy.…”
Section: Discussionmentioning
confidence: 99%
“…To date however, only 23 cases of XLH undergoing spinal surgery for myelopathy have been reported (Hirao et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recent case report revealed that 34-year-old female with vitamin D resistant rickets had extensive ossification of the paraspinal ligaments. The serum concentration of her Pi was low whereas that of Ca was normal [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%